2009
DOI: 10.1098/rspb.2009.1000
|View full text |Cite
|
Sign up to set email alerts
|

How climate change might influence the starvation–predation risk trade-off response

Abstract: Climate change within the UK will affect winter starvation risk because higher temperatures reduce energy budgets and are likely to increase the quality of the foraging environment. Mass regulation in birds is a consequence of the starvation -predation risk trade-off: decreasing starvation risk because of climate change should decrease mass, but this will be countered by the effects of predation risk, because high predation risk has a negative effect on mass when foraging conditions are poor and a positive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Changes in late-breeding-season food availability due to changes in climate, land-use, or management could therefore affect body condition of juvenile wheatears. This could affect the quality of post-juvenile molt (Dawson et al 2000), starvation risk on Fair Isle, predator avoidance behavior due to the need for increased risk taking under conditions of nutritional stress (Cresswell et al 2009), and the rate and extent of fat and muscle accumulation for autumn migration (Bairlein and Hu¨ppop 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in late-breeding-season food availability due to changes in climate, land-use, or management could therefore affect body condition of juvenile wheatears. This could affect the quality of post-juvenile molt (Dawson et al 2000), starvation risk on Fair Isle, predator avoidance behavior due to the need for increased risk taking under conditions of nutritional stress (Cresswell et al 2009), and the rate and extent of fat and muscle accumulation for autumn migration (Bairlein and Hu¨ppop 2004).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, food availability is critical for winter survival of birds (Fretwell 1972;Newton 1980), throughout its influence on the satisfaction of energy demands, on building up body reserves to overcome fasting periods (e.g., the long winter night or during cold spells ;Blem 1990;Biebach 1996), and on breeding performance the following spring (Robb et al 2008). Cresswell et al (2009) have shown that the increase of 6.5°C from 1995 to 2005 in mean daily winter temperature decreased the starvation risk of great tits in England (birds responded to this scenario decreasing their body mass), while Rogers and Reed (2003) showed how the groundfeeding finch Junco hyemalis maximizes winter survival probability by integrating multiple environmental factors affecting starvation risk including temperature (but also snowfall frequency and food availability). Cresswell et al (2009) have shown that the increase of 6.5°C from 1995 to 2005 in mean daily winter temperature decreased the starvation risk of great tits in England (birds responded to this scenario decreasing their body mass), while Rogers and Reed (2003) showed how the groundfeeding finch Junco hyemalis maximizes winter survival probability by integrating multiple environmental factors affecting starvation risk including temperature (but also snowfall frequency and food availability).…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies of great tits have also reported a temporal decline in adult body mass, with decreases of 0.036 g/year over the period 1968-2002 and 0.023 residual g/year (Cresswell et al 2009). In comparison, the decrease in adult body mass found here was between 0.013 and 0.015 g/year.…”
Section: Temporal Changes In Body Size Traitsmentioning
confidence: 99%